Safety evaluation of the food enzyme endo‐1,4‐β‐xylanase from the genetically modified Trichoderma reesei strain NZYM‐ER - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2022)
Abstract The food enzyme endo‐1,4‐β‐xylanase (4‐β‐d‐xylan xylanohydrolase; EC 3.2.1.8) is produced with the genetically modified Trichoderma reesei strain NZYM‐ER by Novozymes A/S. The genetic modifications do not give rise to safety concerns. The food enzyme is considered free from viable cells of the production organism and its DNA. The food enzyme is intended to be used in brewing processes, distilled alcohol production, grain treatment for the production of starch and gluten fractions and for palm oil production. Since residual amounts of total organic solids (TOS) are removed by distillation, in palm oil production and in grain treatment for the production of starch and gluten fraction, dietary exposure was only calculated for brewing processes. Dietary exposure to the food enzyme TOS was estimated to be up to 0.09 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 1,051 mg TOS/kg bw per day, the highest dose tested, which when compared with the estimated dietary exposure, results in a margin of exposure of at least 11,400. A search for similarity of the amino acid sequence of the food enzyme to known allergens was made and no match was found. The Panel considered that, under the intended conditions of use (other than distilled alcohol production) the risk of allergic sensitisation and elicitation reactions by dietary exposure cannot be excluded, but the likelihood for this to occur is considered to be low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.